1978
DOI: 10.1002/hlca.19780610408
|View full text |Cite
|
Sign up to set email alerts
|

5, 7‐Dihydroxy‐8‐methoxy‐chroman‐4‐on aus dem Zwiebelwachs von Eucomis comosa

Abstract: (23.11.78) 5,7-Dihydroxy-8-methoxy-chroman-4-one from the Bulb Wax of Eucomis comosa SummaryFrom the bulb wax of Eucomis comosa (HOUTT.) WEHRH. (Liliaceae) 5,7-dihydroxy-8-methoxy-chroman-4-one (1) was isolated. The structure was confirmed by direct comparison with a synthetic specimen. 1 is the first natural chroman-4-one which is unsubstituted in the heterocyclic ring.1. Einleitung. -Aus dem Wachs der Zwiebeln einiger Eucomis-Arten sind eine grossere Zahl von phenolischen Verbindungen isoliert worden, die au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Other authors (see refs. Heller, M. (1978), Woszczyna, A. (1980), Woszczyna, A. and Betkowski, W. (1982)) have also concluded that anisotropic models have in general a vacuum stage near an unavoidable initial singularity in which the energy-momentum tensor has no influence on the cosmic evolution.…”
Section: Nouraddin Mostafapoormentioning
confidence: 98%
“…Other authors (see refs. Heller, M. (1978), Woszczyna, A. (1980), Woszczyna, A. and Betkowski, W. (1982)) have also concluded that anisotropic models have in general a vacuum stage near an unavoidable initial singularity in which the energy-momentum tensor has no influence on the cosmic evolution.…”
Section: Nouraddin Mostafapoormentioning
confidence: 98%
“…5,7-Dihydroxy-8-methoxy-chroman-4-one has been isolated from Eucomis comosa by Heller and Tamm [50]. The co-occurrence of homoisoflavones with identical substitution in ring A of 13 and 108 is striking, and no biogenetic inference has been drawn from this observation.…”
Section: Biosynthesis Of Homoisoflavonoidsmentioning
confidence: 99%
“…The dichloromethane extract yielded the seven known compounds (7, 10, 19, 20, 21, 22 and 23) and ve novel triterpenoids (24 [the aglycone of 25], 26, 27, 28 and 29). The methanol extract was found to contain the known homoisoavonoid 30 as well as nine novel lanosterol glycosides (31)(32)(33)(34)(35)(36)(37)(38)(39). 18 Eucomis autumnalis (Mill.)…”
mentioning
confidence: 99%
“…(as Eucomis punctata L'Herit). 37 The bulb wax of Eucomis comosa yielded the chroman-4-one 52 38 while an examination of the methanol extract of the fresh, air-dried bulbs gave ve homoisoavanones (47,48,50 and both the E and Z form of 6). 39 The same study included Eucomis pallidiora Baker subsp.…”
mentioning
confidence: 99%